Indonesianomics: An Integrated Natural, Ethnobotanical, and Scientific Resources Database of Indonesia - Ichsan, Mochammad; Kholilah, Tsaniyah Nur; Aslahah, Binti Hifdhotun Al; Mardiyanti, Lely (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.534, 2017)
A critical barrier to enhance the natural resource and ethnobotany plants conservation appears. While open-accessible databases containing natural resource and ethnobotany application have been established in a number of other countries, there is currently no such online database in Indonesia that even known as a mega-biodiversity country. Indonesianomics is a public repository that provides integrated and comprehensive information about Indonesia’s natural resources in regard to their medical and ethnobotanical applications. The user can enhance the data by submitting data. This database obtains 100 iTerm records, 999 iJamu records, 4.937 iPlant records, 6.776 iCompound records, 125 iTaxonomy records, 5 iPeptide records, 100 iEthnobotany records, 20 iReference records, 3.972 iJournal records, 5 iBook records, 12 iAuthor records, and 75 iAffiliation records. Indonesianomics present as the starting point to enhance community-driven platform by curating database for further natural product resource in Indonesia. Available at https://indonesianomics.hamfaro.or.id.